Fungal Metabolomics: A Comprehensive Approach to Understanding Pathogenesis in Humans and Identifying Potential Therapeutics - Vinicius Alves; Daniel Zamith-Miranda; Susana Frases; Joshua D. Nosanchuk (Journal of Fungi)
Metabolomics has emerged as a transformative tool in the study of microbes, including pathogenic fungi, facilitating the identification of unique metabolic profiles that elucidate their pathogenic mechanisms, host interactions, and treatment resistance. This review highlights key applications of metabolomics in understanding fungal metabolites essential for human virulence, such as mycotoxins produced by various fungal species, including Aspergillus fumigatus (gliotoxin, fumagillins) and Candida species (phenylethyl alcohol, TCA cycle metabolites), and secondary metabolites that contribute to pathogenicity. It also explores the metabolic adaptations of fungi in relation to drug resistance and biofilm formation, revealing alterations in key metabolic pathways during infection, as seen in C. albicans and C. auris. Furthermore, metabolomics aids in deciphering host–pathogen interactions, showcasing how fungi like Cryptococcus neoformans and Candida modify host metabolism to promote survival and evade immune responses. The study of antifungal resistance mechanisms has also benefited from metabolomic approaches, identifying specific metabolite patterns that signify resistance, such as in Candida albicans and Candidozyma (Candida) auris, and informing new therapeutic strategies. The integration of metabolomics with other omics technologies is paving the way for a comprehensive understanding of fungal biology and pathogenesis. Such multi-omics approaches are crucial for discovering new therapeutic targets and developing innovative antifungal treatments. Thus, the purpose of this review is to provide an overview of how metabolomics is revolutionizing our understanding of fungal pathogenesis, drug resistance, and host interactions, and to highlight its potential for identifying new therapeutic targets and improving antifungal strategies.